Inside Out: Archaeal Ectosymbionts Suggest a Second Model of Reduced-Genome Evolution - Nicks, Trevor; Rahn-Lee, Lilah (Frontiers in Microbiology, 2017)
Reduced genome symbionts and their organelle counterparts, which have even smaller genomes, are essential to the lives of many organisms. But how and why have these genomes become so small? Endosymbiotic genome reduction is a product of isolation within the host, followed by massive pseudogenization and gene loss often including DNA repair mechanisms. This phenomenon can be observed in insect endosymbionts such as the bacteria Carsonella ruddii and Buchnera aphidicola. Yet endosymbionts are not the only organisms with reduced genomes. Thermophilic microorganisms experience selective pressures that cause their genomes to become more compact and efficient. Nanoarchaea are thermophilic archaeal ectosymbionts that live on the surface of archaeal hosts. Their genomes, a full order of magnitude smaller than the Escherichia coli genome, are very small and efficient. How have the genomes of nanoarchaea and late-stage insect endosymbionts, which live in drastically different environments, come to mirror each other in both genome size and efficiency? Because of their growth at extreme temperatures and their exterior association with their host, nanoarchaea appear to have experienced genome reduction differently than mesophilic insect endosymbionts. We suggest that habitat-specific mechanisms of genome reduction result in fundamentally different pathways for these two groups of organisms. With this assertion, we propose two pathways of symbiosis-driven genome reduction; isolation-symbiosis experienced by insect endosymbionts and thermal-symbiosis experienced by nanoarchaea.